Results of snow load monitoring system tests in winter 2020/21 - V. А. Lobkina; A. A. Muzychenko (Лëд и снег, 2022)
A system of the snow load monitoring is proposed to be used for reducing the risks of damage and destruction of buildings under the influence of snow load. In the winter season of 2020/21, a variant of the snow load monitoring system being developed in the Sakhalin branch of the Far Eastern Geological Institute of the Far Eastern Branch of the Russian Academy of Sciences was tested in the city Yuzhno-Sakhalinsk. The observation program included continuous obtaining of values of snow load on the ground during the season. The two monitoring systems were used for the observations. The snow thickness on the site of System № 1 was periodically cut along the contour, while the System № 2 worked under natural conditions of snow accumulation. Observations were carried out from December 16, 2020 to March 31, 2021. The thaw, which lasted from February 16 to 19, 2021, deteriorated the conditions of the experiment. The prolonged rise in the air temperature resulted in heating of the snow thickness down to its full depth, and the snow cover began to melt. Meltwater reached positions of the Systems, which led to a malfunction in their functioning. That is why we present here the results of observations for the period from December 16, 2020 to February 19, 2021 i.e. before the ceasing the experiment caused by the thaw. When evaluating results of the observations having been made, the average values and standard deviations of the transmitted readings were calculated and compared with the reference parameters. For the last ones, data on the amount of solid precipitation for the whole season obtained at the Yuzhno-Sakhalinsk meteorological station were used. For the observational period, the mean deviation value and the standard error of the mean of the snow load on the ground were calculated as the following: the system № 1 – (6±5%), and the system № 2 – (–1±6%). Mean deviation from the reference value was equal to 0.06 kN/m2 for the System № 1 is, and 0.01 kN/m2 for the System № 2, which was consistent with the error of strain gauges (tension sensors) used in the system with account for the standard deviation error. The error ±0.1 kN/m2 was chosen as an acceptable error of the monitoring system, that was reasoned by the current loads standards.